GC-MS and in silico analyses revealed the potential inhibitory activity of compounds isolated from Ciplukan herb (Physalis angulata L.) targeting GLUT-4 receptors - Rita Rakhmawati, Setyanto Tri Wahyudi, Mae Sri Hartati Wahyuningsih, Mustofa Mustofa, Ahmad Hamim Sadewa (Journal of Applied Pharmaceutical Science, 2024)
The escalating prevalence of diabetes mellitus (DM), a major global health threat and one of the top 10 causes of mortality, is a worrying trend. Prolonged hyperglycemia in people with diabetes triggers oxidative stress, leading to accelerated tissue damage, increased levels of free radicals, and the onset of complications. Our initial exploration of Physalis angulata L, using bioassay-guided isolation and C2C12 insulin resistance monitoring, revealed the compound’s ability to increase cellular glucose uptake. Consequently, there is an urgent need for further drug discovery efforts aimed at deciphering the mechanism of action of compounds targeting GLUT4 receptors in silico. The focus of this study was to predict the mechanism of action of compounds against the AS160 protein to facilitate GLUT4 translocation to the cell surface. Using GC-MS analysis and molecular docking via Autodock Vina, a mixture of blind and targeted docking approaches, isolated compounds were identified. Notably, this study marks the first identification, to the best of our knowledge, of campesterol and stigmasterol in P. angulata L herbs by GC-MS analysis. Through in silico simulations, campesterol and stigmasterol show promising potential in the treatment of type 2 diabetes by targeting the glucose transporter GLUT4 via facilitating GLUT4 translocation. Given their favorable pharmacokinetic properties, these phytoconstituents are potential hypoglycemic agents.
Keywords: AS160 protein, diabetes mellitus, GC-MS, GLUT4, in silico, phytosterol